Transformational Leadership and Knowledge Sharing on Employee Efficiency Mediated by Employee Satisfaction - Irwan Raditya (International Journal Labs, 2022)
Along with the development of the logistics industry, of course, this requires companies to increase competitiveness in various ways. Some of the ways that can be done are to increase employee job satisfaction for work efficiency to get better. However, there are still related problems, namely a poor leadership system and a lack of employee social interaction. This study aims to examine and analyze the relationship between transformational leadership and knowledge sharing on employee efficiency mediated by employee satisfaction with the employees of PT Surya Madistrindo in Jakarta. The sample used in this study amounted to 138 respondents and was collected by purposive sampling. The test was carried out using the Structural Equation Model (SEM) method. The result of this study is that transformational leadership has a positive relationship with employee efficiency, with a result of 79.1%, and is mediated by employee satisfaction with an outcome of 55.9%. It can be concluded that the leadership should provide advice and motivation directly to employees to improve their work efficiency. At the same time, knowledge sharing positively correlates with employee efficiency with results of 40.3% and is mediated by employee satisfaction with results of 58.4%. It can be concluded that leaders should hold events that increase social interaction between employees with the hope that employees will feel satisfied and create good work efficiency.